Odpowiedzi

2010-01-15T21:01:20+01:00
A.(a-3b)(a+3b)= a^2 - 9b^2
d.(x^2y+2xy^2)(x^2y-2xy^2)= x^4y^2 - 4x^2y^4
b.(1/2m+n^2)(1/2m-n^2)= 1/4m^2 - n^4
c.(p/3-3q)(3q+p/3)=(p/3-3q)(p/3+3q)=p^2/9 - 9q^2
2010-01-15T21:07:35+01:00
Korzystam ze wzoru skróconego mnożenia :
(a - b)(a +b) = a² - b²

a.(a-3b)(a+3b)= [a² -(3b)²] = a² - 9b²

b.(1/2m+n^2)(1/2m-n^2)=
(1/2m + n²) (1/2m - n²) = (1/2m)² - (n²)² = 1/4m² - n⁴

c.(p/3-3q)(3q+p/3)= (p/3-3q)(p/3 + 3q)= (p/3)² -(3q)²= 1/9p² - 9q²

d.(x^2y+2xy^2)(x^2y-2xy^2)=
= (x²y + 2xy²) (x²y - 2xy²) = (x²y)² - (2xy²)² = x⁴y² - 4x²y⁴